2011
DOI: 10.1016/j.yebeh.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Semantic association investigated with functional MRI and independent component analysis

Abstract: Semantic association, an essential element of human language, enables discourse and inference. Neuroimaging studies have revealed localization and lateralization of semantic circuitry making substantial contributions to cognitive neuroscience. However, due to methodological limitations, these investigations have only identified individual functional components rather than capturing the behavior of the entire network. To overcome these limitations, we have implemented group independent component analysis (ICA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 118 publications
15
91
0
4
Order By: Relevance
“…Therefore, we may interpret this as a strategy to cope with the increased perception of difficulties in selecting the right concepts. Interestingly, this interpretation is coherent with recent reports where anterior and posterior portions of the left inferior frontal cortex have been postulated to be important for the top-down controlled retrieval of concepts and the subsequent selection of highly activated candidates, respectively (Schuhmann, Schiller, Goebel, & Sack, 2012;Kim, Karunanayaka, Privitera, Holland, & Szaflarski, 2011;Lau, Phillips, & Poeppel, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we may interpret this as a strategy to cope with the increased perception of difficulties in selecting the right concepts. Interestingly, this interpretation is coherent with recent reports where anterior and posterior portions of the left inferior frontal cortex have been postulated to be important for the top-down controlled retrieval of concepts and the subsequent selection of highly activated candidates, respectively (Schuhmann, Schiller, Goebel, & Sack, 2012;Kim, Karunanayaka, Privitera, Holland, & Szaflarski, 2011;Lau, Phillips, & Poeppel, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Recent neuropsychological and neuroimaging evidence highlights the possibility that difficulties in the process of lexical selection might not only affect grammatical processing but even impair the patients' ability to produce a well-formed narrative discourse at the macrolinguistic level. For example, it has been shown that the top-down controlled selection and/or retrieval of contextually adequate words from the mental lexicon (likely implemented in a set of cortical and subcortical areas including but not limited to the left inferior frontal cortex; Hagoort, 2005;Kim, Karunanayaka, Privitera, Holland, & Szaflarski, 2011;Lau, Phillips, & Poeppel, 2008;Whitney, Kirk, OĘźSullivan, Lambon Ralph, & Jefferies, 2011) triggers the unification of lexical information into an overall representation that spans multiword utterances. Similarly, in Marini and Urgesi (2012), repetitive Transcranial Magnetic Stimulation applied over the dorsal portion of the anterior left inferior frontal gyrus reduced the levels of lexical informativeness of narratives produced by a group of healthy individuals that, in turn, caused the production of errors of global coherence.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings could suggest a role for the left SMG in the processing of rhythmic, phonologically encoded arithmetic facts in memory (i.e., processing deeply encoded arithmetic facts as a type of rhyme). However, other studies point to a role for the SMG in the processing of semantic associations, both in the context of arithmetic (Grabner et al, 2012) and linguistic processing (Kim et al, 2011), suggesting a more complex and abstract function underlying SMG activity. Thus, SMG's involvement in arithmetic fact retrieval may represent a more "mature" calculation mechanism comprising semantic memory search processes that rely on phonological, timing, and semantic processing mechanisms.…”
Section: Summary and Interpretationmentioning
confidence: 96%